2016
DOI: 10.4103/0019-5545.183782
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of modern electroconvulsive therapy on subjective memory in patients with mania or depression

Abstract: Context:Although electroconvulsive therapy (ECT) is considered a very effective tool for the treatment of psychiatric diseases, memory disturbances are among the most important adverse effects.Aims:This study aimed to assess prospectively early subjective memory complaints in depressive and manic patients due to bilateral, brief-pulse ECT, at different stages of the treatment, compare the associations between psychiatric diagnosis, sociodemographic characteristics, and ECT characteristics.Settings and Design:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We found that 15 out of 16 studies reported that major depressive disorder in unipolar or bipolar depression was the indication for treatment in the majority of patients. One study reported 59.3% of their sample being treated for mania 12 . Two studies reported use in patients with schizophrenia and schizoaffective disorders, although it was unclear whether these patients were treated for their depressive or primary psychotic symptoms 13 , 14 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that 15 out of 16 studies reported that major depressive disorder in unipolar or bipolar depression was the indication for treatment in the majority of patients. One study reported 59.3% of their sample being treated for mania 12 . Two studies reported use in patients with schizophrenia and schizoaffective disorders, although it was unclear whether these patients were treated for their depressive or primary psychotic symptoms 13 , 14 …”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used tool for measuring subjective memory change was the SSMQ, with eight studies using all or part of this scale 6 , 12 , 15 20 . This is an 18-item questionnaire assesses various aspects of subjective memory on a Likert scale from −4 (much worse) to +4 (much improved), providing a total score comparing current memory with a previous time point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroconvulsive therapy (ECT) is effective during manic episodes; however, because it is an invasive procedure and has negative side effects on memory ( 49 ), the indications are limited. Exuberant behaviour that needs to be controlled immediately, catatonic symptoms, resistance to current treatment and causes that limit the use of drugs such as pregnancy and old age are among the indications of ECT ( 50 , 51 ).…”
Section: Other Options In the Treatment Of Acute Manic Episodesmentioning
confidence: 99%